Manajemen Promosi Yayasan Izzatuna Putra Palembang Dalam Meningkatkan Jumlah Santri - Dava Adriansah; Hasril Atieq Pohan (ScidacPlus, 2023)
This research is entitled: Promotion Management of Izzatuna Putra Palembang Foundation in Increasing the Number of Santri. The purpose of this research is to: Know and describe the management carried out by the Izzatuna Foundation in increasing the number of students. This study uses a type of qualitative research. Data collection techniques in this study are using interviews, observation and documentation. The theory used in this study is the theory of Philip Kotler. The data analysis technique used in this study is the technique of Miles and Huberman, namely data reduction, data presentation and drawing conclusions. The results showed that the promotional activities carried out by the Izzatuna Foundation had been carried out well. The implementation of these promotional activities carried out both directly and indirectly through print media, word of mouth information, visits to residents' homes as a whole, visits to schools as a whole and collaboration with the community, running Islamic boarding schools programs and using social media. Evaluation of the implementation of promotional activities for the Izzatuna Foundation every new school year is shown by the achievement of student targets that have been set for each year but in reality the student targets have not been achieved so far because students are more interested in attending public schools, so the number of students or santri incoming each year has decreased. Suggestions for the Izzatuna Foundation should always maintain communication and cooperation and always create cohesiveness with various parties both internally and externally, because with good cooperation it can contribute to the development of pesantren promotion, so that pesantren promotion programs can be communicated and carried out well and get results which is satisfying.